2013
DOI: 10.1002/adfm.201301628
|View full text |Cite
|
Sign up to set email alerts
|

On‐Chip Fabrication of Paclitaxel‐Loaded Chitosan Nanoparticles for Cancer Therapeutics

Abstract: The use of solvent‐free microfluidics to fine‐tune the physical and chemical properties of chitosan nanoparticles for drug delivery is demonstrated. Nanoparticle self‐assembly is driven by pH changes in a water environment, which increases biocompatibility by avoiding organic solvent contamination common with traditional techniques. Controlling the time of mixing (2.5–75 ms) during nanoparticle self‐assembly enables us to adjust nanoparticle size and surface potential in order to maximize cellular uptake, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 39 publications
1
77
0
1
Order By: Relevance
“…Microfluidics is attractive for making chitosan nanoparticles. Although fast mixing in microfluidics remains a challenge due to its laminar flow characteristics (Rhee et al, 2011), it has been demonstrated computationally (Kamat et al, 2015) and experimentally (Cetin et al, 2014;Chen et al, 2014b;Majedi et al, 2014) that introducing active mixers can facilitate rapid mixing through chaotic advection and diffusion. Cetin et al designed a microfluidic device (Fig.…”
Section: Natural Polymer Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Microfluidics is attractive for making chitosan nanoparticles. Although fast mixing in microfluidics remains a challenge due to its laminar flow characteristics (Rhee et al, 2011), it has been demonstrated computationally (Kamat et al, 2015) and experimentally (Cetin et al, 2014;Chen et al, 2014b;Majedi et al, 2014) that introducing active mixers can facilitate rapid mixing through chaotic advection and diffusion. Cetin et al designed a microfluidic device (Fig.…”
Section: Natural Polymer Nanoparticlesmentioning
confidence: 99%
“…For example, chitosan/cytosine-phosphodiester-guanine oligodeoxynucleotide (CpG ODN) NPs prepared using a microfluidic method exhibited enhanced cellular uptake and immunostimulatory response in comparison to the NPs synthesized via the conventional bulk mixing method (Chen et al, 2014b). (Majedi et al, 2014).…”
Section: Natural Polymer Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…pH-sensitive polymers are polyelectrolytes whose coiled chains expand upon ionization, in response to changes in environmental pH, and their hydrodynamic volume increases dramatically due to electrostatic repulsion from the charges generated (anions or cations) along the backbone (Figure 2) (Qiu & Park, 2001;Majedi et al, 2013). Two main strategies exist in the design of pH-sensitive drug delivery systems: the use of polymeric systems with ionizable groups attached to the backbone that their conformational or solubility properties changes in response to changes in pH values and the use of polymers bearing acid-sensitive bonds whose cleavage triggers the release of drug molecules attached to the polymer backbone, modification of the polymer charge or the exposure of targeting ligands (n ¼ 4 independent experiments) (Majedi et al, 2013).…”
Section: Ph-sensitive Polymersmentioning
confidence: 99%
“…During the past two decades, a substantial amount of work has been published that this polymer is very suitable for preparation of nano-and microparticles for controlled drug release and offers valuable advantages as a drug delivery carrier for both small molecular drugs, like nicotine (Hui Wang, George, Bartlett, Gao, & Islam, 2017), paclitaxel (Majedi et al, 2014), and macromolecules, such as RNA (Ragelle et al, 2014), DNA (Gan, Wang, Cochrane, & McCarron, 2005). A wide range of drug formulations including gels, capsules, tablets, inhalations have been manufactured by CS.…”
Section: Chitosan Nanoparticles As a Pulmonary Delivery Systemmentioning
confidence: 99%